Drama with children - Phillips, Sarah (Oxford Univ. Press, 1999)
The book provides practical ideas for introducing drama activities into the English class, including role play, mime, chants, puppets, and short plays. As well as develping speaking and pronunciation, drama helps children to develop self-confidence and express their imagination, personalities, and creativity.